Sex-specific associations of reservoir–excess pressure parameters with age and subclinical vascular remodeling. Issue 4 (1st April 2023) - Gimblet, Colin J.; Armstrong, Matthew K.; Nuckols, Virginia R.; DuBose, Lyndsey E.; Holwerda, Seth W.; Luehrs, Rachel E.; Lane, Abbi D.; Voss, Michelle W.; Pierce, Gary L.
Abstract : Objective: Central artery reservoir pressure and excess pressure (XSP) are associated with cardiovascular disease (CVD) events and mortality. However, sex differences in the trajectory of central reservoir pressure and XSP with advancing age and their relations with vascular markers of subclinical CVD risk are incompletely understood. Therefore, we tested the hypothesis that central reservoir pressure and XSP would be positively associated with advancing age and vascular markers of subclinical CVD risk in men and women. Method: Healthy adults ( n = 398; aged 18–80 years, 60% female individuals) had central (carotid) artery pressure waveforms acquired by applanation tonometry. Reservoir pressure and XSP peaks and integrals were derived retrospectively from carotid pressure waveforms using custom written software. Carotid artery intimal–medial thickness (IMT) was measured by ultrasonography, and aortic stiffness was determined from carotid–femoral pulse wave velocity (cfPWV). Results: Reservoir pressure peak, reservoir pressure integral and XSP integral were higher with age in both men and women ( P < 0.05), whereas XSP peak was lower with age in men ( P < 0.05). In women, both reservoir pressure peak ( β = 0.231, P < 0.01) and reservoir pressure integral ( β = 0.254, P < 0.01) were associated with carotid artery IMT, and reservoir pressure peak was associated with cfPWV ( β = 0.120, P = 0.02) after adjusting for CVD risk factors. Conclusion: Central artery reservoir pressure and XSP were higher with advancing age in men and women, and reservoir pressure peak was associated with both carotid artery wall thickness and aortic stiffness in women but not men. Central reservoir pressure peak may provide some insight into sex differences in vascular remodeling and subclinical CVD risk with advancing age in healthy adults.